hands prosthesis controlled by electromyographic signals (Innovation & Development in Engineering and Applied Science, 2020)
The electronic design of a right-hand prosthesis is presented. To do this, a model, previously developed, was used, whose geometry consists of the assembly of the palm and the five fingers of the hand articulated in such a way that the flexion and extension movements of the fingers can be carried out. The functioning of the prosthesis is controlled by myoelectric signals that drive a servo-motor located in the palm. National Instruments Multisim software was used to design and simulate the signals involved in the process. As a result, a hand prosthesis activated by myoelectric impulses of the muscles was obtained, with the ability to execute the tasks of the thin clamp and thick clamp, being able to detect points of high tightening by means of pressure sensors at the tip of the fingers